Optical filter based on metal-insulator-metal plasmonic coupled cavities. Issue 1 (March 2021) - Lounis, A; Hocini, A; Ben salah, H
Abstract: In this study, an optical filter based on a plasmonic metal-insulator-metal (MIM) coupled waveguide resonator is simulated and investigated. Using the proposed structure leads to realizing a filter function between targeted wavelengths by manipulating the appropriate geometrical parameters of the resonators. Two-dimensional FDTD-based simulation is implemented to analyze the filter properties. The filter proposed proves to be a potential candidate for highly integrated optical circuit applications.